2018
DOI: 10.1186/s12866-018-1274-9
|View full text |Cite
|
Sign up to set email alerts
|

The palatine tonsil bacteriome, but not the mycobiome, is altered in HIV infection

Abstract: BackgroundMicrobial flora in several organs of HIV-infected individuals have been characterized; however, the palatine tonsil bacteriome and mycobiome and their relationship with each other remain unclear. Determining the palatine tonsil microbiome may provide a better understanding of the pathogenesis of oral and systemic complications in HIV-infected individuals. We conducted a cross-sectional study to characterize the palatine tonsil microbiome in HIV-infected individuals.ResultsPalatine tonsillar swabs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 70 publications
0
43
1
Order By: Relevance
“…Changes in the availability of oxygen, nutrients, and the pH-mediating effect of saliva [96] can promote the growth of different organisms, and conversely, these organisms can be involved in their own small niche construction [97] via biofilm formation and nutrient metabolism, which can produce effects both within the oral cavity (Table 1, Figure 2) and systemically (Table 2, Figure 2). Some researchers have chosen to study all these niches in parallel to compare them against each other [3,8,9], some have selected individual sites with particular focuses on localized dysbiosis in disease states [98][99][100][101][102][103][104][105][106], and others have used an oral rinse approach to capture an overall view of the oral cavity [10][11][12].…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the availability of oxygen, nutrients, and the pH-mediating effect of saliva [96] can promote the growth of different organisms, and conversely, these organisms can be involved in their own small niche construction [97] via biofilm formation and nutrient metabolism, which can produce effects both within the oral cavity (Table 1, Figure 2) and systemically (Table 2, Figure 2). Some researchers have chosen to study all these niches in parallel to compare them against each other [3,8,9], some have selected individual sites with particular focuses on localized dysbiosis in disease states [98][99][100][101][102][103][104][105][106], and others have used an oral rinse approach to capture an overall view of the oral cavity [10][11][12].…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
“…The tongue was also targeted as a potential segment in diagnostic tools that would perhaps incorporate the microbiomes of the full gastrointestinal tract to detect pancreatic cancer [105]. The palatine tonsils were explored in HIV-infected patients to better understand the oral and systemic complications of the disease, and it was shown that the bacteriome was indeed significantly altered in infected individuals, but the mycobiome was not [106].…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
“…Deep sequencing and statistical analysis were performed as described previously. 52 Briefly, the library targeting the 16S rRNA V3 and V4 regions was prepared using the primer set consisting of 341 F (5′-CCTACGGGNGGCWG-CAG-3′) and 806 R (5′-GACTACHVGGGTATCTAATCC-3′) according to the manufacturer's protocol (http://jp.support.illumina.com/ content/dam/illumina-support/documents/documentation/ chemistry_documentation/16s/16s-metagenomic-library-prepguide-15044223-b.pdf) for sequencing on Illumina MiSeq (Illumina, San Diego, CA, USA). The library was sequenced with 2 × 300-bp paired-end reads using MiSeq v3 reagent kits (Illumina, San Diego, CA, USA), resulting in a total of 1,611,524 reads with a mean of 134,294 ± 12,918 sequences per sample.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…A total of 48 families were detected in all three groups. The median number of observed families was lower in CD patients (23, interquartile range (IQR) 19.5-24.5) and UC patients (25, compared with healthy participants (28, (Fig. S3).…”
Section: Japanese Ibd Patients Had Altered Gut Microbiomementioning
confidence: 99%
“…Sequencing data were processed using CLC Genomics Workbench 11.0.1 and CLC Microbial Genomics Module 3.5 (Qiagen, Redwood City, CA, USA) [25]. Overlapping paired-end reads were merged and trimmed, and chimeric reads were ltered using default parameters.…”
Section: Sequence and Statistical Analysesmentioning
confidence: 99%